Identification and temporal expression profiles of cuticular proteins in the endoparasitoid wasp, Microplitis mediator. (6th August 2019) - Volovych, Olga; Lin, Zhe; Du, Jie; Jiang, Hong; Zou, Zhen
Abstract: Recently, parasitoid wasp species Microplitis mediator has evoked increasing research attention due to its possible use in the control of Lepidoptera insects. Because insect development involves changes in cuticle composition, identification and expression analysis of M. mediator cuticular proteins may clarify the mechanisms involved in parasite development processes. We found 70 cuticular proteins from the M. mediator transcriptome and divided them into seven distinct families. Expression profiling indicated that most of these cuticular protein genes have expression peaks specific for one particular developmental stage of M. mediator . Eggs and pupae have the highest number of transcriptionally active cuticular protein genes (47 and 52 respectively). Only 12 of these genes maintained high expression activity during late larval development. Functional analysis of two larval proteins, MmCPR3 and MmCPR14, suggested their important role in the proper organization of the cuticle layers of larvae. During M. mediator larval development, normal cuticle formation can be supported by a limited number of cuticular proteins.